1986
DOI: 10.1017/s0022172400065943
|View full text |Cite
|
Sign up to set email alerts
|

Experimental plague infection in South African wild rodents

Abstract: SUMMARYSusceptibility studies were undertaken to determine the response of some South African wild rodent species to experimental plague (Yersinia pestis) infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Plague resistance in these R. rattus populations would therefore be an example of rapid evolution (Altizer et al, 2003), which may be explained by the high virulence of plague bacteria (Stenseth et al, 2008) and the short generation time of the black rat (approximately 0.5 years; J.-M. Duplantier, unpublished data). Evolution of plague resistance may not be restricted to this system, as variability in resistance related to plague occurrence has been described in other recent plague foci: Onychomys leucogaster (Thomas et al, 1988) and Microtus californicus (Quan and Kartman, 1962) in North America; Mastomys natalensis in South Africa (Shepherd et al, 1986). Unlike these native species, the black rat was introduced to Madagascar a few thousand years ago, and consequently displays relatively low levels of neutral genetic variability, especially in the central highlands (Tollenaere et al, 2010), but this does not appear to have prevented rapid evolution (see also Koskinen et al, 2002;Dlugosch and Parker, 2008).…”
Section: Comparison Of Plague Susceptibility Between Plague Focus Andmentioning
confidence: 95%
“…Plague resistance in these R. rattus populations would therefore be an example of rapid evolution (Altizer et al, 2003), which may be explained by the high virulence of plague bacteria (Stenseth et al, 2008) and the short generation time of the black rat (approximately 0.5 years; J.-M. Duplantier, unpublished data). Evolution of plague resistance may not be restricted to this system, as variability in resistance related to plague occurrence has been described in other recent plague foci: Onychomys leucogaster (Thomas et al, 1988) and Microtus californicus (Quan and Kartman, 1962) in North America; Mastomys natalensis in South Africa (Shepherd et al, 1986). Unlike these native species, the black rat was introduced to Madagascar a few thousand years ago, and consequently displays relatively low levels of neutral genetic variability, especially in the central highlands (Tollenaere et al, 2010), but this does not appear to have prevented rapid evolution (see also Koskinen et al, 2002;Dlugosch and Parker, 2008).…”
Section: Comparison Of Plague Susceptibility Between Plague Focus Andmentioning
confidence: 95%
“…In Mandoto (peneplain area) no difference was found [33], whereas in Betafo (mountainous area) genetic differences were observed between rats from rice field populations compared to those from houses and sisal hedges [34]. This resistance seems to be passed on to offspring as also suggested for M. natalensis [31]. A 32-base pair deletion in the chemokine receptor 5 gene (CCR5) used by HIV-1 to enter cells has been proposed to confer resistance to HIV, smallpox, and plague infections [35].…”
Section: Main Factors Impacting the Epidemiology Of Plague In Madagascarmentioning
confidence: 99%
“…For example, although our study indicated that R. rattus was the rodent most commonly found in the huts in our study areas (91.4%), Þve (8.6%) other species of rodents were captured. Among the noncommensal rodents captured in our study, only M. natalensis has been evaluated for its susceptibility to Y. pestis infection (Isaä cson et al 1983, Shepherd et al 1986). Although the plague susceptibility has not been investigated under laboratory conditions, A. niloticus is thought to be involved in the ecology of plague (Hopkins 1949, Kilonzo and Mhina 1983, Gratz 1999) elsewhere in East Africa and was the most commonly encountered noncommensal rodent species collected in our study.…”
Section: Table 3 Median and Range Of No Of Fleas Of Rodents Collectmentioning
confidence: 99%